Preparation of cobalt crystals with various morphologies and the catalytic performance of platinum-on-cobalt crystal for the selective hydrogenation of nitrobenzene. Issue 32 (3rd August 2020) - Pei, An; Ruan, Luna; Fu, Huan; Liu, Jun; Zeng, Li; Zhang, Huan; Hua, Jingrong; Zhu, Lihua; Chen, Bing Hui
Abstract : The Pt/Co-No catalyst exhibited the best catalytic property (yield to aniline-95.8%) due to high Pt dispersion and nano-synergy effect between Pt- and Co-related species. Abstract : Herein, hierarchical cobalt crystals with a dendritic-like shape were successfully synthesized without adding any capping agent or surfactant, represented as Co-No- T, where T represents 60 °C, 90 °C, or 120 °C. The effects of the hydrothermal temperature on the size and length of cobalt dendrites was also investigated. Besides, the morphology of the hierarchical cobalt crystals, such as leaf-like, mushroom-like, and marshmallow-like, was also modulated at room temperature (RT) by adding different surfactants (No, polyvinylpyrrolidone-PVP, or cetyltrimethylammonium bromide-CTAB, represented as Co-No-RT, Co-PVP-RT, Co-CTAB-RT, respectively). Numerous Pt/Co bimetallic nanocatalysts (Pt/Co-X- T, where X and T represent the surfactant-No, PVP, or CTAB and hydrothermal temperature of 60 °C, 90 °C, or 120 °C, respectively) with the hierarchical cobalt crystals as a support were prepared via a simple galvanic replacement reaction. Moreover, the catalytic performance of these Pt/Co-X- T catalysts for the selective hydrogenation of nitrobenzene was evaluated. The Pt/Co-No-RT catalyst exhibited the best catalytic property (yield to aniline-95.8%) due to high platinum dispersion and nano-synergy effects between platinum- and cobalt-related species. Furthermore, the recycling of the Pt/Co-X- T bimetallic catalysts can be easily achieved via magnetic separation.